Monitoring protein phosphorylation by acrylamide pendant Phos-Tag™ in various plants - Bekesova, Slavka; Komis, George; Krenek, Pavel; Vyplelova, Petra; Ovecka, Miroslav; Luptovciak, Ivan; Illes, Peter; Kucharova, Anna; Samaj, Jozef (Frontiers in Plant Science, 2015)
The aim of the present study is to rationalize acrylamide pendant Phos-Tag™ in-gel discrimination of phosphorylated and non-phosphorylated plant protein species with standard immunoblot analysis, and optimize sample preparation, efficient electrophoretic separation and transfer. We tested variants of the method including extraction buffers suitable for preservation of phosphorylated protein species in crude extracts from plants and we addressed the importance of the cation (Mn2+ or Zn2+) used in the gel recipe for efficient transfer to PVDF membranes for further immunoblot analysis. We demonstrate the monitoring of Medicago sativa stress-induced mitogen activated protein kinase (SIMK) in stress-treated wild type plants and transgenic SIMKK RNAi line. We further show the hyperosmotically-induced phosphorylation of the previously uncharacterized HvMPK4 of barley. The method is validated using inducible phosphorylation of barley and wheat α-tubulin and of Arabidopsis MPK6. Acrylamide pendant Phos-Tag™ offers a flexible tool for studying protein phosphorylation in crops and Arabidopsis circumventing radioactive labeling and the use of phosphorylation specific antibodies.